1997
DOI: 10.1084/jem.185.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Protects Lenses against Cataract Induced by Transforming Growth Factor-β (TGFβ)

Abstract: Cataract, already a major cause of visual impairment and blindness, is likely to become an increasing problem as the world population ages. In a previous study, we showed that transforming growth factor-β (TGFβ) induces rat lenses in culture to develop opacities and other changes that have many features of human subcapsular cataracts. Here we show that estrogen protects against cataract. Lenses from female rats are more resistant to TGFβ-induced cataract than those from males. Furthermore, lenses from ovariect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 34 publications
5
59
1
1
Order By: Relevance
“…First, oestrogen receptor messenger RNA has been found in the human lens, suggesting that oestrogen has a direct effect on the lens. 30 In laboratory rat models, oestrogen has been found to protect against cataract induced by transforming growth factor-beta 6 and by methylnitrosourea. 7 Significantly, oestrogen has also been shown to have antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, oestrogen receptor messenger RNA has been found in the human lens, suggesting that oestrogen has a direct effect on the lens. 30 In laboratory rat models, oestrogen has been found to protect against cataract induced by transforming growth factor-beta 6 and by methylnitrosourea. 7 Significantly, oestrogen has also been shown to have antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, evidence from laboratory studies has suggested that it may protect against the development of cataract. 6,7 Cataract is a major cause of poor vision and blindness, 8 with the worldwide prevalence estimated to increase from 16 million cases in 1997 to 40 million by the year 2020. 9 Any factor that reduces the incidence of cataract may thus be of great public health significance.…”
Section: Introductionmentioning
confidence: 99%
“…1,18 The protective role of oestrogen in cataractogenesis has been well studied in in vivo and in vitro conditions. 5,6,12,15 This study elucidates the quick protective role of 17b-oestradiol against H 2 O 2 -induced oxidative stress in cultured LECs.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen protects the lens against TGF-binduced cataract in the lens culture system. 5 Oestrogen has also been reported to exert protective effects in the rat model of age-related cataracts induced by methyl nitrosourea (MNU). 6 Oxidative stress is widely recognized as one of the major causes of cataract.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an increased prevalence of cataracts in postmenopausal women, and estrogen has been reported to be effective in preventing age-related cataracts. [5][6][7][8] Estrogen is a hormone that participates in regulating calcium (Ca) levels in the body, and postmenopausal women experience a drop in estrogen secretion. Bone resorption is regulated by estrogen, and a decrease in estrogen level leads to a decrease in vitamin D. Since vitamin D enhances Ca 2+ absorption from the small intestine, [9][10][11][12] postmenopausal women are at greater risk of osteoporosis and hypercalcemia/ hypocalcemia via the dysfunction in Ca 2+ regulation due to a chronic reduction in circulating estrogen levels.…”
mentioning
confidence: 99%